Copyright Protection of Cinematographic Works Due to Piracy of Spoiler Films Through the TikTok Application - Amrullah, Muchlis; Wahyuni, Ridha (Law Development Journal, 2024)
This study aims to analyze legal protection and legal remedies due to spoiler film piracy through the Tiktok application, referring to Law No. 28 of 2014 concerning Copyright. The phenomenon of violations of film spoiler practices in the form of content through the TikTok platform has a negative impact on creators or copyright holders. Both morally and economically. In this case, of course, legal protection of cinematographic works must be enforced. Although legal regulations related to copyright of cinematographic works are available, in reality many people pirate spoiler films. This study uses a normative juridical method by reviewing theories, concepts, legal principles and related laws and regulations. The results of this study conclude that the protection and enforcement of copyright law for cinematographic works in the form of preventive and repressive, by providing licenses, supervision and law enforcement based on the perspective of Law No. 28 of 2014 concerning Copyright. The study shows that film spoilers in the form of content on the Tiktok application are very easy to use and the government is not firm in supervising electronic system providers, in this case Tiktok. Therefore, more effective supervision and law enforcement are needed to combat future film spoilers.